Anatomical Study of Cutaneous Venous Flow of the Palm. Issue 4 (April 2017) - Kim, Baek-kyu; Kwon, Heeyeon; Imanishi, Nobuaki; Chang, Hak
Abstract : Backgrounds: Various flaps elevated from the palm have been widely used for finger and hand reconstruction. Recently, perforator-based free flaps or venous free flaps have received popularity due to several advantages. The cutaneous venous system has been chosen as the circulatory outlet when designing and harvesting the flap from the palmer area due to the small size and thin nature of the flap. However, there have been few descriptions about the anatomy of the palmar cutaneous veins. A more detailed knowledge will be valuable for elevating various flaps from the palmar area. Methods: Whole-body and hand venography with a contrast medium was performed on 9 fresh cadavers. Dissection and investigation of the skin and subcutaneous tissue were performed using a soft x-ray system with a stereogram. During all the processes that involved elevating the tissue, observations were made on the macroscopic structure of the palmar vein. Results: In the palm, a complex network of veins are connected with the distal branches of the cephalic vein, basilic vein, and dorsal venous arch. The pattern and geometric formation of the venous network in all cases showed distinctive features according to each region of the palm. The venous branches create a network extending to palmar margins and webs between fingers. Conclusions: Venous arrangement should be considered when designing flaps from the palm to prevent venous congestion and safely extend the length of the flap.